A COMPARATIVE ANALYSIS OF THE INDONESIAN AND PHILIPPINE JUDICIAL SYSTEMS: IDENTIFYING THE ROLE OF CUSTOMARY COURTS - Hazar Kusmayanti; Sonny Dewi Judiasih; Dede Kania; Dewi Sulastri (Universitas Lampung, 2025)
Customary dispute resolution institutions in Indonesia and the Philippines serve to provide indigenous peoples with access to justice beyond state courts. This research, employing a normative juridical approach with a descriptive-analytical specification, highlights key differences between the two systems. In Indonesia, customary courts derive recognition from the 1945 Constitution, while in the Philippines, they are explicitly regulated under the Indigenous Peoples’ Rights Act (IPRA) of 1997, leading to greater integration with the national legal system. Indonesian customary courts handle a broader range of disputes, whereas Philippine customary courts primarily focus on land rights and natural resource management. Additionally, Indonesian customary court decisions often face dualism in the application of customary and national law when reviewed by state courts, while Philippine customary court decisions are more systematically recognized and enforced within the formal legal framework.